Hadith #5918 - Sahih al-Bukhari - Al-Haitham bin Abu Sinan (Sahih al-Bukhari)
that he heard Abu Huraira in his narration, mentioning that the Prophet (ﷺ) said, “A Muslim brother of yours who does not say dirty words.” and by that he meant Ibn Rawaha, “said (in verse): ‘We have Allah’s Messenger (ﷺ) with us who recites the Holy Qur’an in the early morning time. He gave us guidance and light while we were blind and astray, so our hearts are sure that whatever he says, will certainly happen. He does not touch his bed at night, being busy in worshipping Allah
Grade: Sahih